Penyuluhan Budaya 5R dan Kesehatan Keselamatan Kerja di PT. Tunggal Indotama Abadi - Ririn Regiana Dwi Satya; Sahat Sinambela; Irman maulana; Nurdeni, Nurdeni (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2022)
Conformite Europene (CE) Marking certification is a certificate that shows a guarantee of product safety and security for users. The problem faced by the company in terms of product exports, especially to the European Market, is the prerequisite for completeness in the form of CE Mark certification. Answering these problems, the purpose of this counseling and mentoring program is the implementation of the 5R Program (Concise, Neat, Clean, Treat, Diligent) to lead to the acquisition of certification. In addition, Occupational Health and Safety (K3) is very necessary for every institution or organization in preventing accidents and occupational diseases. Based on PP RI Number 50 of 2012. 5R and K3 The solution offered through community service by lecturers and students is to provide counseling and assistance to build a culture and arrangement of a clean and healthy work environment, as well as improve work environment management so that it is effective and efficient. . Outcome plans (in the form of services, systems, products, etc.) that are targeted are counseling and assistance with training modules, displays and reports along with photos and activity banners